Investigation on demand response of Indian electrical energy micro grid. (2021) - Sasikumar, C.; Jaganathan, S.; Suryaprakash, S.
Abstract: Long-term and short-term forecasting of load has been actual task to scheduling power in different level. Various Technology play a vital role to forecast the demand and analysis. This Work introduces easiest method to analyse the daily electrical consumption data over the period of years. The facility to use historical data about electric energy daily consumption to agree refining the energy effectiveness of various buildings, as fit as benefit to spot complications associated to wastage of energy. In this article, concerned in analysing the energy consumption of IT buildings in Coimbatore, and propose a Weekly study of consumption using open source tool. This paper analysed the system with data and get future energy consumption with different machine learning analysis.